Chromosomes of South American Bufonidae (Amphibia, Anura) Chromosomes of South American Bufonidae (Amphibia, Anura) - Brum Zorrilla N.; Saenz F. A. (Caldasia)
Karyotypes of eight of South American Bufonidae were studied: B. ictericus, B. spinulosus spinulosus, B. arenarum, B. g. fernandezae, B. g. d'orbignyi, B. crucifer, B. paracnemis and B. marinus. In all species 2n = 22 chromosomes were found. Neither heteromorphic pairs of chromosomes nor bivalents with characteristic morphology and behavior of sex chromosomes during male meiosis were observed in any species. Karyotypes of eight of South American Bufonidae were studied: B. ictericus, B. spinulosus spinulosus, B. arenarum, B. g. fernandezae, B. g. d'orbignyi, B. crucifer, B. paracnemis and B. marinus. In all species 2n = 22 chromosomes were found. Neither heteromorphic pairs of chromosomes nor bivalents with characteristic morphology and behavior of sex chromosomes during male meiosis were observed in any species.